An immune risk score predicts progression-free survival of melanoma patients in South China receiving anti-PD-1 inhibitor therapy—a retrospective cohort study examining 66 circulating immune cell subsets - Chi, Peidong; Jiang, Hang; Li, Dandan; Li, Jingjing; Wen, Xizhi; Ding, Qiyue; Chen, Linbin; Zhang, Xiaoshi; Huang, Junqi; Ding, Ya (Frontiers in Immunology, 2022)
Immune checkpoint blockade inhibitor (ICIs) therapy provides significant survival benefits for malignant melanoma. However, a proportion of patients were observed disease progression after the first few treatment cycles. Therefore, it is urgent to find the convenient and accessible indicators that can indicate whether patients can benefit from ICIs therapy. We used flow cytometry to determine the absolute values of 66 immune cell subsets in peripheral blood of melanoma patients before treatment with anti-PD-1 inhibitors. LASSO cox regression model was followed to investigate the efficacy of each subset in predicting the progression-free survival. We found a prognostic immune risk score composed with CD1c+ dendritic cells and three subsets of T cells (CD8+CD28+, CD3+TCRαβ+HLA-DR+, CD3+TCRγδ+HLA-DR+) which had a higher prognostic power than that of individual features (AUC = 0.825). Using this model, patients of training cohort (n=29) could be divided into high-risk group and low-risk group with significantly different in mean progression-free survival (3.6 vs 12.3 months), disease control rate (41.2% vs 91.7%), and objective response rate (17.6% vs 41.6%). We also validate the performance of this model in validation cohorts (n=20). We developed a nomogram for clinical use which integrated the four-immune cell-subset based classifier and four clinicopathological risk factors to predict which patients might benefit from anti-PD-1 antibodies inhibitors. The immune cell subsets we examined were numerous and comprehensive. The prognostic immune risk score including the innate immune and adaptive immune cell populations could provide an accurate prediction efficacy in malignant melanoma patients with ICIs therapy.